Effect of Fertilisers on Forage Production in Ravine Lands - Singh, Bakhshish; Verma, Balvir; Monappa, K. (Indian Forester, 1970)
Seven fertiliser treatments consisting of 20 kg Nitrogen as Ammonium Sulphate, 20 kg P2O5 as Superphosphate, and 20 kg K2O as Sulphate of Potash per hectare, singly as well as in different combinations, were tried for a period of 4 years in the ravine lands along the river Mahi at the Soil Conservation Research Station, Vasad (Gujarat) to study their effects on grassland production, quality of fodder and economics, etc., as compared to the control-where no fertilisers were applied. Results indicate that combined application of N & P gave significantly higher mean forage yield. Cumulative effect of phosphates in the later years was better than that of nitrogen, while potash depressed the forage yield. The various treatments of fertilisers had neither any significant effect on percentage botanical composition of the grass species, nor on their chemical composition (total N per cent and crude protein per cent as compared to control). Dichanthium annulatum gave significantly higher N per cent, and crude protein per cent under the treatments of N, K & PK as compared to NP and NPK. None of the fertiliser applications proved to be economical as compared to the Control.